Centro de acopio cafetero en el municipio de dolores- Tolima (2023)
The feasibility study for the creation of the coffee collection center for the municipality of Dolores Tolima, is important, since it seeks to establish and present a proposal for the channeling of coffee from said area, exposing a possible solution for the distribution, marketing and competitiveness of the product at the level municipal, obtaining a series of benefits with the implementation of the project, such as son, increase profits, training on innovation, management of resources, government aid and interaction of small coffee producers in the municipality.